Assessing the Feasibility of Wedding Organizer Services: A Case Study of Swana Wedding Organizer in Cikarang - Apriyanih, Cindy; Riswandari, Imas Candra; Tanjung, Kartika Permata Sari; Nugraha, Nerissa Arviana; Zifanzani, Salina (Review: Journal of Multidisciplinary in Social Sciences, 2025)
This study analyzes the feasibility of a wedding organizer business, focusing on Swana Wedding Organizer as a case study. The increasing demand for wedding services along with changes in modern lifestyles has made wedding organizers a solution for couples who want to plan a stress-free wedding. The research method used is descriptive with a qualitative approach, including observation, surveys, and interviews. The results show that Swana Wedding Organizer offers varied and high-quality services, at affordable prices for the middle to upper class. Despite facing stiff competition, marketing strategies through social media and collaboration with other vendors have increased visibility and reputation. Significant revenue fluctuations indicate good growth potential, indicating that Swana Wedding Organizer is feasible to run and has positive prospects in the competitive wedding industry, while contributing theoretically by enriching the literature on business feasibility in the service sector and practically by providing insights for entrepreneurs on how to integrate marketing strategies, service quality, and vendor collaboration to achieve sustainable competitiveness.